2019
DOI: 10.3390/sym11040493
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Fuzzy CODAS Method Based on Fuzzy Envelopes for Hesitant Fuzzy Linguistic Term Sets: A Case Study on a Personnel Selection Problem

Abstract: Fuzzy multi-criteria decision-making (MCDM) methods are useful and reliable for multi-criteria selection problems under uncertain and imprecise situations. In these methods, if decision-makers hesitate among several linguistic terms, hesitant fuzzy linguistic term sets (HFLTSs), represented by a set of successive linguistic terms instead of single linguistic terms, may be more appropriate to make evaluations. The notion of a fuzzy envelope for the HFLTSs is a beneficial tool that can be directly applied to fuz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 83 publications
(88 reference statements)
0
23
0
Order By: Relevance
“…However, the CODAS technique gives results when crisp values are available. In order to present an MCDM technique, which enables to deal with uncertainties, this approach was extended in later studies (Keshavarz Ghorabaee et al, 2016a;Yalçın & Pehlivan, 2019;Vinodh & Wankhede, 2020;Roy et. al., 2019) with the help of the fuzzy set theory introduced by Zadeh (1965).…”
Section: The Fuzzy Codas Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…However, the CODAS technique gives results when crisp values are available. In order to present an MCDM technique, which enables to deal with uncertainties, this approach was extended in later studies (Keshavarz Ghorabaee et al, 2016a;Yalçın & Pehlivan, 2019;Vinodh & Wankhede, 2020;Roy et. al., 2019) with the help of the fuzzy set theory introduced by Zadeh (1965).…”
Section: The Fuzzy Codas Techniquementioning
confidence: 99%
“…Although the fuzzy CODAS technique that is a part of the proposed integrated fuzzy model is a novel multi-criteria decision-making (MCDM) approach, it has been observed that it has been applied in some studies for solving decision-making problems in various fields. For example; evaluation of IT technology alternatives for a university (Dahooie et al, 2020), evaluation of environmental quality (Ouhibi & Frikha, 2020), the selection of vehicle shredding facility location (Simic et al, 2021), evaluation of renewable energy alternatives , evaluation of personnel selection problem (Yalçın & Pehlivan, 2019), market segment evaluation (Keshavarz Ghorabaee et al, 2016a). The number of studies using the F-CODAS technique is very limited and none of these papers dealt with decision-making problems encountered in the field of logistics.…”
Section: Introductionmentioning
confidence: 99%
“…The results depicted in Table 8 were further analyzed with the Spearman's rank correlation coefficients. The coefficients stimulate a profound understanding of the degree of agreement [79,80] between the ranks generated by the proposed technique as compared to the other four techniques. The coefficients that are listed in Table 9 are higher than 0.7, which showed that the result of the proposed technique is approximately consistent with that of WSM, TOPSIS, and PCBU.…”
Section: Comparison With Other Techniquesmentioning
confidence: 99%
“…Grey additive ratio assessment (ARAS-G) and the stepwise weight assessment ratio analysis (SWARA) were integrated to derive the criteria weights and to determine the final ranking order of all candidates. Yalçın and Yapıcı Pehlivan [42] used the hesitant fuzzy linguistic terms to express the evaluation opinions of experts to deal with the personnel selection problem. In order to justify the usefulness of this method, fuzzy WASPAS (Weighted Aggregated Sum Product Assessment), fuzzy ARAS, fuzzy EDAS (Evaluation based on Distance from Average Solution), fuzzy TOPSIS, and fuzzy WASPAS were used to analyze and evaluate the personnel selection results by using the same data.…”
Section: Literature Reviewmentioning
confidence: 99%